Past and present activities and future strategy of bryophyte conservation - Hallingback, T.; Tan, B. C. (Phytotaxa, 2014)
A review of past and present progresses in bryophyte conservation worldwide is attempted. The strategy and action program in bryophyte conservation in the future are also presented.